Impression Management Komunikasi Lintas Agama Di Sorong, Papua Barat - Nurdin, Ali; Ahmadi, Ahmadi; Suhartini, Rr.; Mustain, Mustain; Wakhid, Ali Abdul (AL-ADYAN, 2022)
Indonesia as a country with a diversity of religions provides part of a strong guideline in the society. The purpose of this study is to describe the management of impressions in inter-religious communication in Sorong, West Papua. The approach of research uses a phenomenology of descriptive-qualitative type with the perspective of dramaturgy theory. Moreover, the data were collected through interviews with religious leaders of Papua, while the observations were made to understand the situation of social interaction in society as well as documentation related to research themes. Furthermore, the data analysis is by grouping information, making categories, and producing findings. Meanwhile, the results of this study will describe that the process of managing impressions in interreligious communication in the Sorong, West Papua is the appearance of stage impressions, appearances, and behavioral styles. Stage impression management is done externally and internally. In addition, the external stage performance was carried out through the Religious Communication Forum (FKUB/Forum Komunikasi Umat Beragama) meeting, while the internal stage was held in a meeting at a place of worship. As for the appearance and style of behavior based on local Papuan customs by the traditional guidelines and religious teachings adopted. Therefore, the overall management of impressions by religious communities as a social capital that could minimize horizontal conflict in the name of religion